DAMPAK PEMEKARAN KEPENGHULUAN TERHADAP PEMBANGUNAN INFRASTRUKTUR KEPENGHULUAN SUNGAI MAJO PUSAKO KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR TAHUN 2015-2016 - Bahar, Rasihan Setia; Febrina, Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Kepenghuluan Sungai Majo Pusako is one of the Pemekaran villages in Kubu Babussalam Subdistrict, Rokan Hilir Regency which does not only have a Positive impact on the Implementation of the Kepenghuluan Government independently but also a negative impact. the formulation of the problem that can be taken is what is the impact of the expansion of Kepenghuluan on the Development of the Majo Pusako River and what are the factors that influence the development in Kepenghuluan Majo Pusako River. This study aims to describe the impact of the expansion of Kepenghuluan on the Development of the Majo Pusako River and to describe the factors that influence the development in Kepenghuluan Sungai Majo Pusako. This study uses the concept of Arif Roesman Efendy about Regency/ City Region Expansion. Primary information sources (informants) are determined by purposive sampling and the data needed is collected by interview and literature study techniques.The impact of Kepenghuluan P separation is intended for the construction of transportation facilities in Kepenghuluan Sungai Majo Pusako has not been carried out properly. Problems The construction of irrigation facilities in Kepenghuluan Sungai Majo Pusako is more directed to irrigation facilities to increase the yield of community rice, Training and guidance facilities, work skills and capital need to obtain support from the Rokan Hilir District Government, the community felt a very positive impact, namely the ease of obtaining business capital assistance. With comprehensive and integrated social development, the life of rural communities will improve the welfare of life in a sustainable manner. The first focus of the Government of Kepenghuluan Majo Pusako River is on the development of Health Services infrastructure. Development that focuses on building infrastructure that can help people to carry out every religious activity. Factors influencing Development in Kepenghuluan Sungai Majo Pusako are the Boundary Area of Conflict Limit, Ownership Status, namely Kepohuluan Sungai Majo Pusako Office Still renting from the community since 2015-2016. Infrastructure problems in Kepenghuluan Majo Pusako River caused complaints from the public with increasing operational costs and daily living expenses in Kepenghuluan Majo Pusako River.Keywords: Impact, Kepenghuluan, Development